2018
DOI: 10.3390/cells7020014
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Saccharomyces cerevisiae as a Model for Understanding RAS Proteins and their Role in Human Tumorigenesis

Abstract: The exploitation of the yeast Saccharomyces cerevisiae as a biological model for the investigation of complex molecular processes conserved in multicellular organisms, such as humans, has allowed fundamental biological discoveries. When comparing yeast and human proteins, it is clear that both amino acid sequences and protein functions are often very well conserved. One example of the high degree of conservation between human and yeast proteins is highlighted by the members of the RAS family. Indeed, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 309 publications
(452 reference statements)
0
45
0
1
Order By: Relevance
“…This can be attributed to the fact that yeasts, being eukaryotes are quite similar to humans in terms of genes and other cellular pathways. It has been observed that the genes that regulate cellular processes in humans have equivalents that control cell division in yeasts as well which makes it very easy for pathogenic yeast species to alter the host cellular machinery (63). Therefore, this study has unravelled the potential mimicry candidates in fungal pathogens which was not well established till now.…”
Section: Motif Mimicrymentioning
confidence: 96%
“…This can be attributed to the fact that yeasts, being eukaryotes are quite similar to humans in terms of genes and other cellular pathways. It has been observed that the genes that regulate cellular processes in humans have equivalents that control cell division in yeasts as well which makes it very easy for pathogenic yeast species to alter the host cellular machinery (63). Therefore, this study has unravelled the potential mimicry candidates in fungal pathogens which was not well established till now.…”
Section: Motif Mimicrymentioning
confidence: 96%
“…On the other hand, the presence of nutrients in the cellular environment activates TOR complex (TORC), which prevents conjugation of Atg1p and Atg13p [241]. The nutrient availability has also been found to activate Ras signaling in both yeast and mammals [295][296][297]. In mammals, Ras signaling activates protein kinase B (Akt) in a cyclic AMP (cAMP)-dependent manner through adenylate cyclase activation [298].…”
Section: Conservation Of Autophagy Regulation In Yeast Modelsmentioning
confidence: 99%
“…Great advances may beneficiate of simple model organisms enabling to dissect the complex network of genes and protein interactomes. To this end, yeast S. cerevisiae represents an awesome biological model for dissection of complex networks ( Cazzanelli et al, 2018 ) with a variety of molecular and genetic tools. The analysis of genetic interactions and the availability of yeast mutants in genes homolog to oncogenes and oncosuppressors may open to the identification of pathway-level interactions involved in oncogenic risk.…”
Section: Yeast Model and Saga Complexmentioning
confidence: 99%